(untitled) (Medico Legal Update, 2021)
Introduction: Forensic anthropometry dealing with the application of anthropometric measurements of human individual for the purposes of the identification of human remains. Inter and intra population variations can be observed in relation to anthropometric measurements due to factors such as genetic makeup, age, gender and ethnicity and help in the identification of individual in criminal investigations. Method: This is cross sectional study using young adult students of age group 17 to 24 years. Participants enrolled after due consent and stature(S) and forearm length (FAL) were measured using standard anthropometric techniques. SPSS statistical package used to calculate Pearson’s coefficients of correlation and regression equations between stature and the anthropometric variables. Results: There were total 255 participants including 54 (21.18%) males and 201 (78.82%) females. Regression equation for estimation of stature from right forearm length is S = 1.4111 Rt FAL+ 126.72, and from left forearm length is S = 1.3774 Lt FAL+ 128.39. There were strong positive correlations between height and forearm lengths in all regressions (r >0.9; p < 0.0001). Conclusions: The proposed regression equations based on forearm length presented here will simplify the task of stature estimation for adults in clinical forensic medicine or as aids to the identification in criminal investigation in endogenous population. The left forearm length is more accurate in estimating the stature of young adults of western Indian population.